The roles of different forms of IL-15 in human melanoma progression - Di Matteo, Sabina; Munari, Enrico; Fiore, Piera Filomena; Santopolo, Silvia; Sampaoli, Camilla; Pelosi, Andrea; Chouaib, Salem; Tumino, Nicola; Vacca, Paola; Mariotti, Francesca Romana; Ebert, Stefan; Machwirth, Markus; et al. (Frontiers in Immunology, 2023)
Background Melanoma is a lethal skin cancer, and the risk of developing it is increased by exposure to ultraviolet (UV) radiation. The production of cytokines such as interleukin-15 (IL-15), induced by the exposure of skin cells to UV rays, could also promote melanoma development. The aim of this study is to investigate the possible role of Interleukin-15/Interleukin-15 Receptor α (IL-15/IL-15Rα) complexes in melanoma development. Methods The expression of IL-15/IL-15Rα complexes by melanoma cells was evaluated both ex vivo and in vitro by tissue microarray, PCR, and flow cytometry. The presence of the soluble complex (sIL-15/IL-15Rα) in the plasma of metastatic melanoma patients was detected using an ELISA assay. Subsequently, we investigated the impact of natural killer (NK) cell activation after rIL-2 starvation followed by exposure to the sIL-15/IL-15Rα complex. Finally, by analyzing public datasets, we studied the correlation between IL-15 and IL-15Rα expressions and melanoma stage, NK and T-cell markers, and overall survival (OS). Results Analysis of a melanoma tissue microarray shows a significant increase in the number of IL-15+ tumor cells from the benign nevi to metastatic melanoma stages. Metastatic melanoma cell lines express a phorbol-12-myristate-13-acetate (PMA)-cleavable membrane-bound IL-15 (mbIL-15), whereas cultures from primary melanomas express a PMA-resistant isoform. Further analysis revealed that 26% of metastatic patients present with consistently high plasmatic levels of sIL-15/IL-15Rα. When the recombinant soluble human IL-15/IL-15Rα complex is added to briefly starved rIL-2-expanded NK cells, these cells exhibit strongly reduced proliferation and levels of cytotoxic activity against K-562 and NALM-18 target cells. The analysis of public gene expression datasets revealed that high IL-15 and IL-15Rα intra-tumoral production correlates with the high levels of expression of CD5+ and NKp46+ (T and NK markers) and significantly correlates with a better OS in stages II and III, but not in stage IV. Conclusions Membrane-bound and secreted IL-15/IL-15Rα complexes are continuously present during progression in melanoma. It is notable that, although IL-15/IL-15Rα initially promoted the production of cytotoxic T and NK cells, at stage IV promotion of the development of anergic and dysfunctional cytotoxic NK cells was observed. In a subgroup of melanoma metastatic patients, the continuous secretion of high amounts of the soluble complex could represent a novel NK cell immune escape mechanism.